Strategi Manajemen Perubahan Dalam Meningkatkan Disiplin di Perguruan Tinggi - Fithrah Dwi Ananda; Nuri Aslami (Universitas Muhammadiyah Enrekang, 2022)
Change management is a systematic process of applying the knowledge, tools and resources needed to effect change in the people who will be affected by the process. Change management is also understood as an effort taken by managers to manage change effectively, where an understanding of motivation, leadership, group, conflict, communication and discipline issues is needed. Thus, change management should have a good strategy, in accordance with the current situation and conditions or will happen.Change management is very appropriate to do in improving its main discipline in higher education. Because the consequences caused by changes in organizations always result in two things, namely changes for good and changes for destruction. Both of these things can happen due to several reasons that come from within or from outside the institution concerned. Because, change management itself is a process, tool, and technique for managing people through the change process to improve discipline, so that the goals of the institution can be achieved.